Pelatihan Pembelajaran Daring Berbasis Google PlatformUntuk Guru Pada SD Swasta Fitria Rahmah - Subhan Hafiz Nanda Ginting; Dinur Syahputra; M. Rhifky Wayahdi; Rutmian Mariama Hutasoit; Sheila Try Thania (Jurnal Pengabdian kepada Masyarakat Nusantara, 2021)
Google Cloud Platform is a suite of public cloud services offered directly by Google developers. However, after seeing the growth of technology, this application created by Google added a variety of new features. This development brought many positive influences, especially for the world of education. The facts show that the use of learning media with computers makes it possible to implement a more effective teaching and learning process.